PENERAPAN MODEL PEMBELAJARAN KOOPERATIF COURSE REVIEW HORAY (CRH) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TERMOKIMIA DI KELAS XI MIA SMA NEGERI 7 PEKANBARU - Rahma, Zulia Rahma; Rery, Radjawali Usman Rery Usman; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is about applying cooperative learning model Course Review Horay (CRH). It was done to know the increase student achievementon the subject termokimia in class XI MIA SMAN 7 Pekanbaru. The type of this research is experimental research with pretest-postest design. The sample consists of two classes. They are class XI Science 1 as an experimental class and class XI Science 2 as a control class which were decided randomly after doing normality and homogenity test. Experimental class is a class that is applied cooperative learning model Course Review Horay (CRH), while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 3> 1,67, means that the application of cooperative learning model Course Review Horay (CRH) can improve student achievement on the subject of termokimia class XI MIA  SMAN 7Pekanbaru, increase learning of 12,5%.   Keywords: cooperative learning, Course Review Horay (CRH)